2007
DOI: 10.1097/wno.0b013e3180321426
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Growth of an Orbital Schwannoma During Pregnancy

Abstract: An incidentally diagnosed unilateral orbital mass in a 34-year-old woman grew at an accelerated rate during pregnancy with deterioration of visual function. Removed early after delivery by a transcranial approach, the tumor was histologically diagnosed as a richly vascularized cystic schwannoma containing red blood cell components. The accelerated tumor growth was attributed to intratumoral hemorrhage. Although acoustic schwannomas have been reported to enlarge during pregnancy, this phenomenon has only been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…Cystic schwannomas in our patient were highly vascular (Fig. 1d–e) consistent with prior reports in pregnancy-associated orbital schwannoma [1] and that women experience larger, more highly-vascular acoustic schwannoma than men [3]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cystic schwannomas in our patient were highly vascular (Fig. 1d–e) consistent with prior reports in pregnancy-associated orbital schwannoma [1] and that women experience larger, more highly-vascular acoustic schwannoma than men [3]. …”
Section: Discussionsupporting
confidence: 91%
“…There have been isolated case reports of rapid expansion in orbital schwannoma causing visual disturbance during pregnancy [1]. Dr. Harvey Cushing suggested that pregnancy may accelerate the growth in acoustic neurilemmoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…While anecdotal information has suggested tumor growth may be exacerbated by pregnancy, at this time there is insufficient evidence to determine whether pregnancy directly results in increased tumor burden or tumor growth in NF1, NF2, and SWN (Cannon et al., 2018; Dugoff & Sujansky, 1996; Gaughan & Harner, 1993; Lusis et al., 2012; Roth, Petty, & Barald, 2008; Sugo et al., 2007). Furthermore, there is insufficient evidence to suggest that NF2 and SWN are associated with an increased risk for pregnancy complications, birth defects, or contraceptive contraindication.…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…In a systematic review of 1,340 patients with schwannomas within a vestibular location, Youshimoto describes a mean annual growth rate of 1.2 mm/year [7]. It is of interest that pregnancy has been associated as a predisposing factor for the accelerated growth of certain schwannomas, i.e., in the orbital space which is believed to be secondary to haemorrhage within the tumour [8].…”
Section: Discussionmentioning
confidence: 99%